EFFECTS OF ECONOMIC GLOBALIZATION OVER INDIVIDUAL SECURITY - Mirela ATANASIU (Annals: Series on Military Sciences, 2013)
Economic globalization represents just a dimension of such spread phenomenon. Globalization phenomenon has raised contradictory discussions particularly related to the effects it has over the individual security. This is the reason we approach this actual theme aiming to identify and analyze some of these effects affecting the security state perceived on the individual or human groups level. Thus, we will follow the social, economic, psychological etc., direct and indirect, positive and negative effects of economic globalization over the individuals.